Controlling of Time-Overrun in Construction Projects in Iraq - T.A. Khaleel; I.Z. Hadi (Engineering and Technology Journal, 2017)
This paper is about analyzing time overrun in construction projects. The principle targets are centered on researching the causes, effects and strategies for controlling time over-run in development ventures in Iraq. The study has been accomplished based on previous researches in addition to a questionnaire form and case studies. Forty-two factors of time overrun causes under four main responsible parties were distinguished (owner, consultant, contractor, others). Eight major impacts of time overrun were also identified. The questionnaire form was formulated based on the above data and was distributed to the selected respondents which are professionals in construction industry. Depending on the results of the questionnaire form, the major origin of time overrun was found that the contractor is the responsible for most of the time overrun (i.e. Contractor's financial difficulties Shortage of skilled manpower and the other causes related to him). The most important two impacts of time overrun were Increase the cost of the project, Quality degradation and Increasing in overhead expenses, the highest percentage of time-overrun in the nine existed project 319% and the most common causes were (change in economic condition and Company's lack of experience).According to the research findings a management system has been proposed to control on the time overrun in construction projects.